A CLINICAL STUDY TO EVALUATE THE ANTIHYPERTENSIVE EFFECT OF TRINPANCHMOOL KWATH IN MANAGEMENT OF ESSENTIAL HYPERTENSION (AYUSHDHARA, 2020)
The present study was conducted to evaluate the antihypertensive effect of an Ayurvedic formulation Trinpanchmool Kwath in the management of essential hypertension. The study was conducted in 30 patients selected from OPD and IPD of R.G.G. P.G.A.C. and Hospital, Paprola. Patients were randomly divided into three groups. Group- I patients were managed with Trinpanchmool Kwath , Group- II patients were managed with Tab Chlorthalidone and Group– III patients were managed with both Trinpanchmool Kwath and Tab. Chlorthalidone. The results obtained were analysed on the basis of various objective and subjective parameters. However change in blood pressure was the main criteria for assessing the effect of the therapy. Statistically highly significant reduction was observed in systolic and diastolic blood pressure after 45 days of therapy. In Group-I systolic blood pressure reduced by 9.374%, in Group-II systolic blood pressure decreased by 15.46% and in Group-III systolic blood pressure decreased by 16.86%. Similarly in Group-I diastolic blood pressure decreased by 8.195% , in Group-II showed 11.250% reduction and in Group-III diastolic blood pressure decreased by 12.17% after completion of therapy. Results revealed that therapy given in Group-III i.e. the combination of Trinpanchmool Kwath and Tab. Chlorthalidone showed best results as compared to other groups. Group-II, in which patients were managed with Tab Chlorthalidone showed better results over Group-I where only Trinpanchmool Kwath was given to the patients. However statistically highly significant reduction in both systolic and diastolic pressure was observed in all three groups.